Impacts of COVID-19 on the Self-employed - Charlene Marie Kalenkoski; Sabrina Wulff Pabilonia (Global Labor Organization (GLO), 2021)
This study estimates random effects and difference-in-difference-in-differences models to examine the initial impacts of COVID-19 on the employment and hours of unincorporated selfemployed workers using monthly panel data from the Current Population Survey. For these workers, effects were visible in March as voluntary social distancing began, largest in April as complete shutdowns occurred, and slightly smaller in May as some restrictions were eased. We find differential effects by gender that favor men, by marital status and gender that favor married men over married women, and by gender, marital, and parental status that favor married fathers over married mothers. The evidence suggests that self-employed married mothers were forced out of the labor force to care for children as prescribed by gender norms and the division and specialization of labor within households. Remote work and working in an essential industry mitigated some of the negative effects on employment and hours.
Keywords: D1; D13; J1; J16; J2; J23; 330; COVID-19; hours worked; self-employment; entrepreneurship; gender; remote work